Identifikasi Pemodelan Matematis Robot Wall Following - Fahmizal Fahmizal; Muhammad Arrofiq Mail; Afrizal Mayub (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
This paper describes the process to obtain a mathematical model of a wall following robot. A mathematical modeling is carried out as an effort in determining Proportional, Integral, and Derivative (PID) controller parameters using analytic tuning. In this paper, the model approach used is Auto Regressive Exogenous (ARX). The ARX model is a model used to show the effect of control and disturbance on the output of the plant. The result of this research is a mathematical model of wall following robot which is then used to obtain PID controller parameters.